Lower Cretaceous lacustrine successions, North Yellow Sea Basin, eastern China: Rift basin sequence stratigraphy and stacking patterns in response to magmatic activity. (December 2017) - Wang, Ren; Shi, Wanzhong; Xie, Xiangyang; Wang, Liaoliang; Manger, Walter; Busbey, Arthur B.; Xu, Qinghai
Abstract: A series of Mesozoic rift basins formed in eastern China were associated with magmatic activity and subduction along the Eurasia, Izanagi and Pacific plate margins. The impact of magmatic activity on lacustrine sequence development was documented with well-log and 3-D seismic data from the Jupiter Depression in the North Yellow Sea Basin. We identified key surfaces, retrogradational and progradational parasequence sets, and defined the characteristics of systems tracts and the internal sequence components for the Lower Cretaceous (K1 SQ1). A 2-D SEDPAK numerical stratigraphic forward modeling was used to further constrain sequence development in the Jupiter Depression by considering different modeling parameters and the spatial-temporal characteristics of magmatic activity. Modeling results were compared and matched with the sequence architecture observed from seismic and well interpretations. Magmatic activity impacts on the development of the K1 SQ1 sequence in the North Yellow Sea Basin include topographic variation, lake level fluctuation, and sediment supply ratios. Results suggest that magmatic upwelling uplifted the northwestern area of the Jupiter Depression and formed its slope break during the late Jurassic or early Cretaceous. Along with uplifting, relative lake level dropped sharply and lake accommodation was reduced, but with increased sediment supply. Therefore, sediment accumulated along the slope break as a lowstand systems tract. Later on, as lake level continuously rose, transgressive and highstand systems tracts were developed. The proposed stacking pattern provides an analog, and a useful model, for lacustrine sequence development in response to magmatic activities in eastern China and other rift basins of similar tectonic setting. Highlights: Detailed architecture characteristics of sequence were well recognized and described. 2-D stratigraphic modeling matched the well and seismic interpretations. Magmatic activities affect the development of lacustrine sequence. The stacking pattern for lacustrine sequence in response to magmatic activity was proposed.